Characteristics of the Polish Stock Market Correlations - Gałązka, Marek (Charakterystyka korelacji na polskim rynku akcji, 2010)
In this paper a network structure of the Polish Stock Market (PSM), one of the emerging markets, is studied. The conceptions: Minimum Spanning Tree (MST) and Weighted Random Graph (WRG), constructed among companies listed on this stock exchange, are compared. In these models every vertex is a stock and the weight assigned to each edge in WRG is the cross-correlation coefficient. The Influence-Strength (IS) is defined at every vertex in both models: in WRG as the sum of the weights on the edges upon that vertex, in MST as the vertex degree. The IS distribution follows a power law with exponent r = 1.6 in WRG and 5 = 2.2 in MST. The both results show that there must be a few stocks whose price fluctuations can powerfully influence the price dynamics of other stocks in the same market. In both cases these are the same companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 141, s. 128-136
Keywords: emerging markets; scale-free network; complex system; random graph; financial correlations